2020
DOI: 10.1101/2020.07.10.20150755
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Serology in Children with Multisystem Inflammatory Syndrome (MIS-C) associated with COVID-19

Abstract: Objectives: We aimed to measure SARS-CoV-2 serologic responses in children hospitalized with multisystem inflammatory syndrome (MIS-C) compared to COVID-19, Kawasaki Disease (KD) and other hospitalized pediatric controls. Methods: From March 17, 2020 - May 26, 2020, we prospectively identified hospitalized children at Children's Healthcare of Atlanta with MIS-C (n=10), symptomatic PCR-confirmed COVID-19 (n=10), KD (n=5), and hospitalized controls (n=4). With IRB approval, we obtained prospective and residual … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 21 publications
2
9
0
Order By: Relevance
“…We also found that 3 out of 4 tested MIS-C patients seroconverted and had comparable levels of SARS-CoV-2 IgG antibodies to the spike protein as the children with mild SARS-CoV-2 infection and no MIS-C ( Figure 6 A). This result is in line with data from other groups studying antibody responses in MIS-C patients ( Gruber et al., 2020 ; Rostad et al., 2020 ). A possible hypothesis for why some children develop MIS-C is that prior immunity to other viruses could modulate their responses to SARS-CoV-2 infection and give rise to hyperinflammation either by antibody-mediated enhancement or other mechanisms ( Tetro, 2020 ).…”
Section: Resultssupporting
confidence: 92%
“…We also found that 3 out of 4 tested MIS-C patients seroconverted and had comparable levels of SARS-CoV-2 IgG antibodies to the spike protein as the children with mild SARS-CoV-2 infection and no MIS-C ( Figure 6 A). This result is in line with data from other groups studying antibody responses in MIS-C patients ( Gruber et al., 2020 ; Rostad et al., 2020 ). A possible hypothesis for why some children develop MIS-C is that prior immunity to other viruses could modulate their responses to SARS-CoV-2 infection and give rise to hyperinflammation either by antibody-mediated enhancement or other mechanisms ( Tetro, 2020 ).…”
Section: Resultssupporting
confidence: 92%
“…We also found that 3 out of 4 tested MIS-C patients seroconverted and had comparable levels of SARS-CoV-2 IgG antibodies to the spike protein as the children with mild SARS-CoV-2 infection and no MIS-C ( Figure 6A ). This result is in line with data from other groups studying antibody responses in MIS-C patients (Gruber et al, 2020; Rostad et al, 2020). A possible hypothesis for why some children develop MIS-C is that prior immunity to other viruses could modulate their responses to SARS-CoV-2 infection and give rise to hyperinflammation either by antibody-mediated enhancement or other mechanisms (Tetro, 2020).…”
Section: Resultssupporting
confidence: 92%
“…But the remaining one-third of patients who were negative on both tests had come in contact with COVID-19-positive individuals [11]. Rostad et al have performed serological studies in children with MIS-C and compared the results with children who had usual COVID-19 infection, KD and hospital controls [54]. They showed that patients with MIS-C had higher levels of IgG SARS-CoV-2 receptor-binding domain.…”
Section: Laboratory Featuresmentioning
confidence: 99%